2022
DOI: 10.7717/peerj.13495
|View full text |Cite
|
Sign up to set email alerts
|

The effects of isometric hand grip force on wrist kinematics and forearm muscle activity during radial and ulnar wrist joint perturbations

Abstract: The purpose of this work was to investigate forearm muscle activity and wrist angular displacement during radial and ulnar wrist perturbations across various isometric hand grip demands. Surface electromyography (EMG) was recorded from eight muscles of the upper extremity. A robotic device delivered perturbations to the hand in the radial and ulnar directions across four pre-perturbation grip magnitudes. Angular displacement and time to peak displacement following perturbations were evaluated. Muscle activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…As a result, pain can impair proprioception both in the peripheral and central nervous systems. Another possible source of the reposition errors considered here was the increased muscle stiffness ( Holmes et al, 2015 ; Weinman et al, 2021 ; Mannella et al, 2022 ). Increased muscle stiffness during grip-strength tasks may change proprioceptive receptor responses, such as the responses of the muscle spindles, which would impact the wrist joint position sense ( Gregory et al, 1988 ; Bower et al, 2006 ; Holmes et al, 2011 ; Naderi et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, pain can impair proprioception both in the peripheral and central nervous systems. Another possible source of the reposition errors considered here was the increased muscle stiffness ( Holmes et al, 2015 ; Weinman et al, 2021 ; Mannella et al, 2022 ). Increased muscle stiffness during grip-strength tasks may change proprioceptive receptor responses, such as the responses of the muscle spindles, which would impact the wrist joint position sense ( Gregory et al, 1988 ; Bower et al, 2006 ; Holmes et al, 2011 ; Naderi et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have focused on determining how a constant grip force affects wrist joint ROM ( Marshall et al, 1999 ; Dimartino et al, 2004 ) and found that as grip force increased, wrist joint ROM decreased. Increasing grip force was also considered one determinant of wrist stiffness ( Holmes et al, 2015 ; Weinman et al, 2021 ; Mannella et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%